Adoption of Mobile Applications for Self-healthcare Monitoring by the Youth in South Africa - (:unkn) unknown (My University, 2022)
Despite growing recognition of the contribution and availability of mobile applications for self-healthcare monitoring to prevent non-communicable diseases (NCDs), NCDs remain a rising concern amongst the youth in sub-Saharan Africa and South Africa in particular. Indeed, self-healthcare monitoring mobile applications can be used to continuously educate and sensitize people about the need to adopt healthy lifestyles to prevent such diseases. However, the adoption of such applications is influenced by many factors which need to be identified in order to devise strategies to encourage people to adopt such applications. Thus, this study investigated the potential adoption of self-healthcare monitoring mobile applications by the youth in South Africa, using the Unified Theory of Acceptance and Use of Technology (UTAUT) as the theoretical lens. Data, gathered from a convenient sample size of 280 participants, were analysed using the Partial Least Square Structural Equation Modelling. The results revealed that performance expectancy and social influence explained 20.3% of the variance of youth’s behavioural intention to adopt self- healthcare monitoring mobile applications in the South African context, while effort expectancy and facilitating conditions did not have a significant effect. Taking the resulting model into account could lead to an increase in the adoption of self-healthcare monitoring applications in South Africa which could assist in the prevention of NCDs. It is recommended that further studies should test the established factors from this study in other contexts.
Keywords: African Research